Suddenly last summer: how the tourist tsunami hit Lisbon - Malet Calvo, D. (2018)
In this paper, we focus our attention in Portugal’s capital city, Lisbon, and in the recent process of its touristification, which is forcing a collective revision of the city’s identity and its patrimonial narratives, to make sense of the growing contrasts between marginality and centrality, circulation and calm, abandonment and limelight, indigence and affluence, spleen and euphoria. After introducing our theoretical focus on the problem of “urban commons” and the qualitative methodology used in the article, we describe the historical process that led to the transformation of Lisbon: from the Expo’98 mega-event when Lisbon was a peripheral tourism destiny, to the present urban economy that is specialised in tourism and services. We will focus especially in the top-down projects and policies developed during those years and the use of 2008 financial crisis to liberalize many aspects of economy.